Environmentally friendly activities in sports and leisure services as an expression of the corporate social responsibility - Widawska-Stanisz, Agnieszka (Journal of Education, Health and Sport, 2022)
Today’s economic reality requires entrepreneurs to introduce many changes, especially those of an organisational nature. The period following COVID-19 pandemic will require organizations to create new values, and a broader view of responsibility, to build mutual trust, and to adapt to the new reality. This paper introduces the principles of Corporate Social Responsibility (CSR), with a focus on ecology as one of the areas of CSR. It can be seen that the pandemic has accelerated environmental targets in many companies. This is due not only to the regulations aligned with the governmental environmental policy, but to an increasing extent also with changing social expectations. The aim of the article was to demonstrate the applicability of ecological, environment-friendly solutions as an example of CSR in the management of sports and leisure enterprises. CPOR studies show that most young people take responsibility for the state of their environment. The training of the test subjects also plays an important role here (CBOS, Environmental Awareness of Poland, 2020) It is assumed that the introduction of eco-friendly solutions in the operation of sports and leisure businesses is noticed and appreciated only by young participants in physical activity. The survey focuses on specific environmental solutions to create a socially responsible corporate image and how these companies operate in a changing environment. The results of the studies carried out for this paper are intended to help answer the question of the importance of emphasising environmental aspects and adapting to change by integrating eco-innovation into the CSR strategies of sports and leisure companies, whether these solutions are perceived by the purchasers of sports and leisure services, as they affect their image. and whether they lead to better relations with market participants.